The Influence of Salapak Mikroshop Support on the Sustainability of Beginner UMKN in Bandung City - Fikri, Fikri Ziddan Al Qorni; Pramanik, Nuniek Dewi (JAKI : Jurnal Akuntansi, 2025)
This study examines the effect of Salapak Mikroshop support on the business sustainability of new micro, small, and medium enterprises (MSMEs) in Bandung. A quantitative, associative research design was used to test the hypothesized causal relationship between Salapak support (independent variable) and MSME sustainability (dependent variable). Data were collected via closed-ended questionnaires (5-point Likert scale) from a random sample of the 80 micro-entrepreneurs participating in the Salapak program (culinary, fashion, and crafts sectors) and analyzed using SPSS. Validity and reliability tests confirmed that all survey items were sound (Cronbach’s α = 0.960 for Salapak support; 0.922 for sustainability). Multiple regression results showed that Salapak support has a strong, positive, and statistically significant effect on MSME sustainability (β = 0.839, t = 13.531, p < 0.001). The model explains 70.4% of the variance in sustainability (R² = 0.704), indicating that Salapak support is a major determinant, while the remaining 29.6% is due to other factors. These findings imply that Salapak’s initiatives – including enhanced market access, business training/mentoring, and product promotion – substantially improve entrepreneurs’ ability to sustain their businesses. Future research should explore additional factors (e.g., digitalization, capital access) to fully understand MSME sustainability.